MENINGKATKAN HASIL BELAJAR MATEMATIKA DENGAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR KELAS IV - Umamy, Nury Azkiya; Marlina, Marlina; Sari, Nor Lila (ACTION : Jurnal Inovasi Penelitian Tindakan Kelas dan Sekolah, 2025)
ABSTRACT The background to this research was the problem faced by students in understanding the explanations given by teachers who only explained the theory without adding examples that were in accordance with the material given. This study was conducted to improve mathematics learning outcomes with the Problem Based Learning model assisted by class IV picture media. This research is a class action research. The method of data collection is from teacher and student activity sheets at each meeting, while learning outcomes are obtained from evaluation results at each meeting. The type of data is quantitative data in the form of learning outcomes and qualitative data in the form of teacher and student activity observations. The results show that the use of problem-based learning model assisted by image media can improve student learning outcomes. Data analysis techniques are divided into 3, namely: Teacher activity, student activity, and student learning completeness. The learning outcomes are as follows: cycle I teacher activity reached Good criteria with a score of 61.6%, and cycle II meeting III reached Very Good criteria with a score of 85.7%. Student activity in cycle I reached the Active criteria with a score of 65.9%, and cycle II meeting III reached the Very Active criteria with a score of 85%.  The percentage of student learning completeness in cycle I reached 66.7%, and cycle II meeting III reached 85%. ABSTRAK Latar belakang terlaksananya penelitian ini adanya permasalahan pada siswa dalam memahami penjelasan yang diberikan oleh guru yang lebih menerangkan teori saja, tanpa menambahkan contoh yang sesuai dengan materi yang diberikan. Penelitian ini dilaksanakan untuk meningkatkan hasil belajar matematika dengan model Problem Based Learning berbantuan media gambar kelas IV. Penelitian ini merupakan penelitian tindakan kelas. Cara pengambilan data adalah dari lembar aktivitas guru dan siswa di setiap pertemuan, sedangkan hasil belajar didapat dari hasil evaluasi di setiap pertemuan. Jenis data yaitu data kuantitatif berupa hasil belajar dan data kualitatif berupa observasi aktivitas guru dan siswa. Hasil menunjukkan bahwa dengan penggunaan model problem based learning berbantuan media gambar dapat meningkatkan hasil belajar peserta didik. Teknik análisis data terbagi menjadi 3, yaitu: Aktivitas guru, aktivitas siswa, dan ketuntasan belajar siswa. Hasil belajar tersebut sebagai berikut: aktivitas guru siklus I mencapai kriteria Baik dengan skor 61,6%, dan siklus II pertemuan III mencapai kriteria Sangat Baik dengan skor 85,7%. Aktivitas siswa siklus I mencapai kriteria Aktif dengan skor 65,9%, dan siklus II pertemuan III mencapai kriteria Sangat Aktif dengan skor 85%.  Persentase ketuntasan belajar siswa Siklus I mencapai 66,7%, dan siklus II pertemuan III mencapai 85%.